1987
DOI: 10.1007/bf00379310
|View full text |Cite
|
Sign up to set email alerts
|

Hypersensitivity reaction of Brassica nigra L. (Cruciferae) kills eggs of Pieris butterflies (Lepidoptera: Pieridae)

Abstract: Some individual plants of the mustard Brassica nigra in lowland California kill eggs of the Crucifer-specialist herbivores Pieris rapae and P. napi by producing a necrotic zone at the base of the egg, thereby apparently desicating it. This is a typical hypersensitivity reaction, but to an atypical stimulus. The eggs can be "rescued" by maintaining them in a saturated atmosphere. Attempts to demonstrate a bacterial or fungal agent associated with the reaction were unsuccessful.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
111
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(118 citation statements)
references
References 2 publications
7
111
0
Order By: Relevance
“…Eggs of P. brassicae and Pieris napi caused the apparition of a necrotic zone on B. nigra plants, increasing egg mortality (Shapiro and Devay, 1987). This response was only observed in some members of the plant population, illustrating a genetic basis for this mechanism.…”
Section: Egg-induced Responsesmentioning
confidence: 95%
See 2 more Smart Citations
“…Eggs of P. brassicae and Pieris napi caused the apparition of a necrotic zone on B. nigra plants, increasing egg mortality (Shapiro and Devay, 1987). This response was only observed in some members of the plant population, illustrating a genetic basis for this mechanism.…”
Section: Egg-induced Responsesmentioning
confidence: 95%
“…The response to oviposition could thus be due to microorganisms associated with the eggs. However, in both reports of HR-like responses to egg deposition, the authors could not isolate plant pathogens associated with the eggs and concluded that the induction of the necrotic response by bacteria was unlikely (Shapiro and Devay, 1987;Balbyshev and Lorenzen, 1997). In our experiments, we could not detect obvious signs of bacterial disease while we observed the induction of a transcript pattern similar to that caused by the infiltration of high doses of a plant pathogen.…”
Section: Nature Of the Elicitormentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, some plant species show a 'hypersensitive response' to oviposition. When eggs are deposited onto their leaves, the tissue around the egg rapidly turns necrotic and in some cases falls off (Balbyshev and Lorenzen, 1997;Shapiro and DeVay, 1987). Because it no longer transpires, the necrotic tissue can get hot enough to kill the egg.…”
Section: K Potter G Davidowitz and H A Woodsmentioning
confidence: 99%
“…Gall insects are known to disturb the inner architecture of a leaf by inserting their eggs (Hilker et al, 2002b). In a few cases, insect egg deposition was shown to induce a hypersensitive response of plant tissue, a well-known response of plants to phytopathogens (Shapiro and DeVay, 1987;Balbyshev and Lorenzen, 1997). Specific pea (Pisum sativum) lines were shown to form neoplasms in response to bruchid egg deposition (Doss et al, 1995(Doss et al, , 2000.…”
mentioning
confidence: 99%